Theme, Tone, and Atmosphere in the Poetry Anthology of Mata Badik Mata Puisi: Semiotics and Ecocritics Perspectives - Wasniah Wasniah; Sumiyadi Sumiyadi; Ma'mur Saadie (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Literature covers many aspects of education. Literature is also a work of personal experience, and one of the popular forms of literature is poetry. In this study, we analyze the elements of poetry construction, particularly thematic elements, tone, and atmosphere, in the anthologi poetry Mata Badik Mata Puisi by D. Zawawi Imron. The method used is qualitative, based on the method of understanding social phenomena and personal perspectives, then researching to describe, study and explain these phenomena in narrative form. Data management technology researchers perform data reduction, presentation, and concluding. From the results of the analysis, the researchers concluded that the poem: Puisi untuk Aslan and Di Pelosok Maros, has environmental themes. The tone and atmosphere of the whole poem are serious, philosophical, solemn, and full of serenity.